2000
DOI: 10.1128/aem.66.11.5053-5065.2000
|View full text |Cite
|
Sign up to set email alerts
|

Comparative 16S rRNA Analysis of Lake Bacterioplankton Reveals Globally Distributed Phylogenetic Clusters Including an Abundant Group of Actinobacteria

Abstract: In a search for cosmopolitan phylogenetic clusters of freshwater bacteria, we recovered a total of 190 full and partial 16S ribosomal DNA (rDNA) sequences from three different lakes (Lake Gossenköllesee, Austria; Lake Fuchskuhle, Germany; and Lake Baikal, Russia). The phylogenetic comparison with the currently available rDNA data set showed that our sequences fall into 16 clusters, which otherwise include bacterial rDNA sequences of primarily freshwater and soil, but not marine, origin. Six of the clusters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
544
9
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(607 citation statements)
references
References 64 publications
52
544
9
2
Order By: Relevance
“…Collectively, these environmental sequence data in Figure 3 show that similar ActR genes are present among diverse freshwater habitats. Such observations verify our initial prediction based on our previous findings in Sharma et al (2008) and the knowledge that many environmental SSU rRNA studies show that members of the Actinobacteria are widespread in fresh waters (Glockner et al, 2000;Warnecke et al, 2004;Allgaier and Grossart, 2006).…”
Section: Isolate Mwh-uga1 Encodes An Lg1-actrsupporting
confidence: 78%
“…Collectively, these environmental sequence data in Figure 3 show that similar ActR genes are present among diverse freshwater habitats. Such observations verify our initial prediction based on our previous findings in Sharma et al (2008) and the knowledge that many environmental SSU rRNA studies show that members of the Actinobacteria are widespread in fresh waters (Glockner et al, 2000;Warnecke et al, 2004;Allgaier and Grossart, 2006).…”
Section: Isolate Mwh-uga1 Encodes An Lg1-actrsupporting
confidence: 78%
“…In combination with a companion study conducted in the same lake (Glockner et al, 2000), their work demonstrated strong and predictable seasonal changes in the relative abundances of dominant bacterial groups (Actinobacteria, b-Proteobacteria and Bacteroidetes; aka CFB) similar to those detailed here for Emerald Lake. In both studies, a maximum in the relative abundance of the b-Proteobacteria was associated with snowmelt, ice-off and spring mixing, followed by a midsummer peak in Actinobacteria, with peaks in the relative abundances of the Bacteroidetes occurring during periods of mixing, including fall overturn and ice-off (Table 3).…”
Section: Phenology Of Bacteria In High-elevation Aquatic Ecosystemsmentioning
confidence: 89%
“…We demonstrated by FISH the presence of free-living PnecC cells in the pelagic zone of a freshwater habitat. This indicates that many or all of the environmental PnecC sequences collected from the pelagic zones of freshwater habitats (7,10,11,21,27,50) originate from free-living cells; however, it is still not known if these cells represent completely free-living strains or facultative endosymbionts of ciliates. The numerically significant contribution of free-living stages of facultative endosymbionts or facultative parasites of protists (e.g., Legionella spp.)…”
Section: Discussionmentioning
confidence: 99%
“…The monophyletic PnecC cluster is characterized by a high minimum sequence similarity of 98.5% (23) and resembles in this feature the microdiverse clusters of marine bacteria (1, 42). Sequences affiliated with PnecC were previously obtained from endosymbionts of aquatic ciliates (40,44), from many freshwater habitats investigated with culture-independent methods (11,21,27,50), and from strains isolated from several freshwater habitats (23). Reports on the detection of PnecC bacteria in soil or marine systems are lacking.…”
mentioning
confidence: 99%